The Key Enzymes of Carbon Metabolism and the Glutathione Antioxidant System Protect Yarrowia lipolytica Yeast Against pH-Induced Stress - Tatyana I. Rakhmanova; Natalia N. Gessler; Elena P. Isakova; Olga I. Klein; Yulia I. Deryabina; Tatyana N. Popova (Journal of Fungi)
In this study, we first thoroughly assayed the response of the key enzymes of energy metabolism and the antioxidant system in Yarrowia lipolytica yeast at extreme pH. The activity of the tricarboxylic acid cycle enzymes, namely NAD-dependent isocitrate dehydrogenase, aconitate hydratase, NAD-dependent malate dehydrogenase, and fumarate hydratase, NADPH-producing enzymes of glucose-6-P dehydrogenase and NADP-dependent isocitrate dehydrogenase, and the enzymes of the glutathione system was assessed. All the enzymes that were tested showed a significant induction contrary to some decrease in the aconitate hydratase activity with acidic and alkaline stress. It is probable that a change in the enzyme activity in the mitochondria matrix is involved in the regulation of the cellular metabolism of Y. lipolytica, which allows the species to prosper at an extreme ambient pH. It distinguishes it from any other type of ascomycete. A close relationship between the induction of the Krebs cycle enzymes and the key enzymes of the glutathione system accompanied by an increased level of reduced glutathione was shown. The assumption that the increased activity of the Krebs cycle dehydrogenases and promotion of the pentose phosphate pathway at pH stress launches a set of events determining the adaptive response of Y. lipolytica yeast.